2017
DOI: 10.1177/0733464816688310
|View full text |Cite
|
Sign up to set email alerts
|

The Social Environment’s Relationship With Frailty: Evidence From Existing Studies

Abstract: Increasingly, policymakers assume that informal networks will provide care for frail older people. While the literature has mainly discussed the role of the family, broader social networks are also considered to be important. However, these social networks can diminish in later life. This systematic review investigates whether the social environment increases the risk of frailty or helps to prevent it. Findings from 15 original studies were classified using five different factors, which denoted five dimensions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
67
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(77 citation statements)
references
References 61 publications
(130 reference statements)
8
67
0
2
Order By: Relevance
“…We highlighted that these experiences of implicit negative AS should be identified and intervened within campaign to combat ageism because of overwhelming evidence indicating their negative health influence [11]. The determinants of frailty included a variety of physiological changes and/or diseases associated with ageing [50], and several psychological, social and environmental factors in previous studies [55][56][57][58]. However, we also emphasized that such a common but overlooked factor of ageism should be taken seriously in the process of frailty.…”
Section: Discussionmentioning
confidence: 99%
“…We highlighted that these experiences of implicit negative AS should be identified and intervened within campaign to combat ageism because of overwhelming evidence indicating their negative health influence [11]. The determinants of frailty included a variety of physiological changes and/or diseases associated with ageing [50], and several psychological, social and environmental factors in previous studies [55][56][57][58]. However, we also emphasized that such a common but overlooked factor of ageism should be taken seriously in the process of frailty.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, SP is critical to the social environment, a broad concept that also includes social networks, social support, and neighborhood characteristics. There is evidence that a good social environment has a beneficial effect on frailty in later life, meaning that mortality could be reduced by ensuring that elders obtain health-related resources [51].…”
Section: Discussionmentioning
confidence: 99%
“…29 Moreover, social participation and factors such as security, strong social cohesion and neighborhood belongingness 29 are protective and provide balance in community frailty levels. 30 Another frailty predictor is poor physical performance (4-6 points), as assessed using the SPPB. An Italian study with a mean follow-up period of 4.4 years found that poor physical performance (score lower than 8 points) was significantly associated with increased risk of becoming frail and with worsening frailty status.…”
Section: Discussionmentioning
confidence: 99%